(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This thesis analyzes the economic, environmental, and strategic significance of using green energy sources in the electric power supply system. The prospects for increasing the share of renewable energy sources—such as solar, wind, and hydropower — in the electric power sector are examined. In addition, investment mechanisms for the implementation of green energy, existing challenges, and ways to overcome them are substantiated.